The Effectiveness of Student's Worksheet Based On 21st Century Learning Skills to Improve Critical Thinking Skills - Renny Dwijayanti; Etty Soesilowati; Puji Handayati (Indonesia Approach Education, 2022)
This study aims to determine the effectiveness of Student Worksheets (LKM) based on 21st-century learning skills in entrepreneurship courses. The research methodology employed a set pre-test and post-test design with limited studies of students in business education programs selected based on the abilities of up to 15 low-, intermediate, and high-ability students. Pre-test and post-test are used to determine students' critical thinking skills. Data were analyzed descriptively and quantitatively. The results showed that student worksheets based on 21st-century learning skills in entrepreneurship courses were effective as teaching materials since the pre-test and post-test data were normally distributed and the average N-Gain results were in the high category.